Comparative Study of Immunization of White Mice Cells Against Hydatid Cysts Using Excretion/Secretion and Cyst Fluid Antigens II: Fluctuation in average percentage of Leukocytes - Ali, Fathi M.; Aboelhaj, Abdulsalam M. A.; Ali , Waheeda R. (Al-Mukhtar Journal of Sciences, 2008)
Human cystic echinococcosis is a cyclozoonotic infection by larval stage of Echinococcus granulosus . This disease has a world-wide distribution and it causes a big health and economic problems. The difficulties that met scientists in the field are the early diagnosis and treatment of the infection . Therefore , the attentions were directed toward the possibility of producing a vaccine that has the ability to stimulate the immune response against the infection. The aim of this work was also directed in this way. Three antigens were extracted and used in our experimental works, These were : Highly antigenic antigen, the Cyst Fluid (CF) antigen. Highly antigenic-highly specific antigen, the Excretion–Secretion(ES) antigen . The third antigen is a mixture of a (1 : 1) proportion of the above two antigens and called ES/CF antigen. These three antigens were used to immunize the experimental animals (white mice). Three concentrations from each antigen were prepared . The three concentrations were used in white mice in addition to booster dose to stimulate immunity . The percentage of Neutrophils, Lymphocyte, and Monocytes showed fluctuations, while the percentage of the Eosinophils remained in the normal range after 30 days of the immunization . After 90 days of the injection of the challenge dose, there was a clear depression in the percentage of lymphocytes and clear rising in that of Neutrophilis with fluctuation in the percentage of Monocytes and Eosinophils in the immunized animals that had cysts . The results in the positive control of mice before the injection of the challenge dose (the same times of the test in the immunized groups) showed that there were no changes in the average percents of white blood cells. However, there were clear differences after 90 days of infection. There was acute depression in the lymphocytes and acute rise in the Neutrophils and a moderate rise in the Eosinophils and Monocytes, the changes sometimes proportional with the infectivity . The results of the test in infected patients with hydatid cysts showed a clear changes in the average percentages of Eosinophils with a clear increase in these cells , while there were no significant changes in the averages of the other cells.